2017
DOI: 10.1186/s12967-017-1118-7
|View full text |Cite
|
Sign up to set email alerts
|

B cell repertoires in HLA-sensitized kidney transplant candidates undergoing desensitization therapy

Abstract: BackgroundKidney transplantation is the most effective treatment for end-stage renal disease. Sensitization refers to pre-existing antibodies against human leukocyte antigen (HLA) protein and remains a major barrier to successful transplantation. Despite implementation of desensitization strategies, many candidates fail to respond. Our objective was to determine whether measuring B cell repertoires could differentiate candidates that respond to desensitization therapy.MethodsWe developed an assay based on high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Furthermore, although megalin is expressed in human podocytes (34,35), it is not detected in the glomerular subepithelial immune complex and no circulating anti-megalin antibodies are found in patients with iMn (36). in addition, the complement pathway and subclass of igG in this model are still unknown (37)(38)(39). Therefore, it is not equivalent to human iMn.…”
Section: Advances Of the Experimental Models Of Idiopathic Membranousmentioning
confidence: 97%
“…Furthermore, although megalin is expressed in human podocytes (34,35), it is not detected in the glomerular subepithelial immune complex and no circulating anti-megalin antibodies are found in patients with iMn (36). in addition, the complement pathway and subclass of igG in this model are still unknown (37)(38)(39). Therefore, it is not equivalent to human iMn.…”
Section: Advances Of the Experimental Models Of Idiopathic Membranousmentioning
confidence: 97%
“…Whether these observed changes in IGHV genes and IGHD genes may serve as better markers in B-cell immunology requires further investigation. The study by Beausang et al (27) suggested that subjects that responded to de-sensitization therapy had pre-treatment repertoires composed of a larger fraction of class-switched (IgG and IgA) isotypes compared to non-responding candidates, indicating that the measurement of B-cell repertoires may be applied to identify candidates that respond to de-sensitization therapy. In the present study, three patients with acute rejection after kidney transplantation were assessed for the purpose of performing a composition and diversity analysis of the BCR H-CDR3 repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐HLA antibodies may wax and wane over time, resulting in a fluctuating repertoire of unacceptable mismatches and, consequently, also resulting in different proportions of potentially compatible donors from the pool. Acknowledging this, transplant centres may use the cumulative cPRA, which considers anti‐HLA antibodies that have been detected over the entire course of pre‐transplant screening (Beausang et al., 2017; Tinckam et al., 2015). The cumulative cPRA is also dependent on the detection of antibodies, which is itself dependent on laboratory practices.…”
Section: Panel Reactive Antibodies and Opportunities For Consideratiomentioning
confidence: 99%